Three new species of Scyracepon Tattersall, 1905 (Isopoda: Bopyridae) from Pacific islands, with comments on the rarity of bopyrids parasitizing brachyurans - An, Jianmei; Zheng, Wanrui; Liang, Jielong; Paulay, Gustav (Zootaxa, 2020)
Three new species of the bopyrid genus Scyracepon Tattersall, 1905 are described from crabs collected on Pacific Islands: Scyracepon polynesiensis n. sp. from the Society Islands, S. pseudoliomerae n. sp. from the Mariana Islands, and S. biglobosus n. sp. from the Line Islands. The first two were found infesting Xanthias lamarckii and Pseudoliomera sp. (Xanthidae), a new host family for species of Scyracepon, and the last was found parasitizing Schizophrys aspera (Majidae). Scyracepon now includes 11 species, all but one known from single collections, infesting 12 host species in 9 brachyuran families. The discovery of three new species, each rare, suggests that crab parasites are undersampled, and further suggests that the low relative diversity of bopyrids known from brachyurans may partly reflect this undersampling. Keys to all species of Scyracepon and to all 31 genera of Keponinae are provided.